SEISMIC PERFORMANCE ANALYSIS OF A THREE-STORY COLD-FORMED STEEL FRAME USING ANSYS BASED ON SNI 1726:2019 - Jihaan Jamilah; Pio Ranap Tua Naibaho; Hikma Dewita (International Journal of Civil Engineering and Infrastructure, 2026)
Indonesia is located in a region with high seismic activity, making earthquake-resistant structural design an essential consideration in building construction. Cold-formed steel (CFS) has become an attractive structural material due to its lightweight characteristics, high strength-to-weight ratio, ease of fabrication, and construction efficiency. However, its relatively thin cross-section requires further evaluation of its seismic performance, particularly for multi-story buildings. This study aims to analyse the dynamic characteristics and seismic performance of a three-story cold-formed steel frame structure subjected to earthquake loading based on SNI 1726:2019 using ANSYS through the Finite Element Method (FEM). The research involved structural modelling, modal analysis, and earthquake load analysis using the Equivalent Lateral Force (ELF) method. The evaluated parameters included natural frequency, vibration period, structural deformation, interstory drift, and maximum structural stress. The analysis results show that the first-mode natural frequency is 9.9662 Hz with a fundamental vibration period of 0.1003 s. The maximum deformation obtained is 0.169 mm, while the maximum interstory drift reaches 0.0066 mm, which is significantly lower than the allowable limit of 72 mm specified in SNI 1726:2019. Furthermore, the maximum structural stress is 1.5202 MPa, considerably lower than the yield strength of G550 steel (550 MPa), indicating that the structure remains within the elastic range. These findings demonstrate that the analysed three-story cold-formed steel frame possesses adequate stiffness, satisfies the seismic performance requirements of SNI 1726:2019, and can safely withstand the applied earthquake loading. Keywords: Cold-Formed Steel; ANSYS; Finite Element Method; Seismic Performance; Earthquake Load.